A First Chromosomal Characterization of Black-Spotted Pufferfish, Arothron nigropunctatus (Tetraodontifrom; Tetraodonidae) - Reungsing, Montri; Tanomtong, Alongklod; Donbundit, Nattasuda; Sonsrin, Khunapat (Food Agricultural Sciences and Technology, 2020)
The present study aims to analyze concerned karyotype and idiogram of black-spotted pufferfish (Arothron nigropunctatus Bloch & Schneider, 1801). Chromosome was prepared from kidney tissues of fish reared at Phuket Marine Biological Center, Phuket province. The mitotic chromosomes were harvested by the colchicine-hypotonic-fixation-air drying method. Conventional staining and Ag-NOR banding techniques were applied to stain the chromosomes. The results showed that A. nigropunctatus has diploid (2n)=38, the fundamental number (NF) was 72. The types of chromosomes are two large metacentric, ten medium metacentric, eight medium submetacentric, two small metacentric, 12 small submetacentric, and four small telocentric chromosomes. This is the first report of marker chromosome; found that NORs located at the short arm region of the submetacentric chromosome. No cytologically distinguishable sex chromosome was observed. The karyotype formula could be deduced as follows: 2n (38) = Lm2 + Mm10 + Msm8 + Sm2 + Ssm12 + St4